Evaluation of vegetable–faba bean (Vicia faba L.) intercropping under Latvian agro‐ecological conditions. (7th March 2017) - Lepse, Līga; Dane, Sandra; Zeipiņa, Solvita; Domínguez‐Perles, Raul; Rosa, Eduardo AS
Abstract: BACKGROUND: Monoculture is used mostly in conventional agriculture, where a single crop is cultivated on the same land for a period of at least 12 months. In an organic and integrated growing approach, more attention is paid to plant–environment interactions and, as a result, diverse growing systems applying intercropping, catch crops, and green manure are being implemented. Thus, field experiments for evaluation of vegetable/faba bean full intercropping efficiency, in terms of vegetable and faba bean yield and protein content, were set up during two consecutive growing seasons (2014 and 2015). RESULTS: Data obtained showed that the most efficient intercropping variants were cabbage/faba bean (cabbage yield 1.27–2.91 kg m −2, immature faba bean pods 0.20–0.43 kg m −2 ) and carrot/faba bean (carrot yield 1.67–2.28 kg m −2, immature faba bean pods 0.10–0.52 kg m −2 ), whilst onion and faba bean intercrop is not recommended for vegetable growing since it induces a very low onion yield (0.66–1.09 kg m −2 ), although the highest immature faba bean pod yield was found in the onion/faba bean intercropping scheme (up to 0.56 kg m −2 ). CONCLUSION: Vegetable/faba bean intercropping can be used in practical horticulture for carrot and cabbage growing in order to ensure sustainable farming and environmentally friendly horticultural production. © 2017 Society of Chemical Industry